2008
DOI: 10.1097/nmd.0b013e31817108ed
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Its Relationship to Physical Health Functioning in a Sample of Iraq and Afghanistan War Veterans Seeking Postdeployment VA Health Care

Abstract: The relationship between posttraumatic stress and physical health functioning was examined in a sample of Iraq and Afghanistan War veterans seeking postdeployment VA care. Iraq and Afghanistan War veterans (N = 108) who presented for treatment to a specialty postdeployment care clinic completed self-report questionnaires that assessed symptoms of posttraumatic stress disorder (PTSD), chemical exposure, combat exposure, and physical health functioning. As predicted, PTSD symptom severity was significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 16 publications
7
69
1
Order By: Relevance
“…According to the findings of the reviewed articles, the self-care status and ADLs were poor among the veterans who suffered from the PTSD. In all of the studies, the physical functioning (i.e., self-care or ADLS) were lower in the PTSD population in comparison to their non-PTSD counterpart (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Our study is congruent with those demonstrating that the PTSD significantly enhances multiple domains of functional impairment (29,46,47).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to the findings of the reviewed articles, the self-care status and ADLs were poor among the veterans who suffered from the PTSD. In all of the studies, the physical functioning (i.e., self-care or ADLS) were lower in the PTSD population in comparison to their non-PTSD counterpart (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Our study is congruent with those demonstrating that the PTSD significantly enhances multiple domains of functional impairment (29,46,47).…”
Section: Discussionsupporting
confidence: 81%
“…Three studies investigated the relationship between the PTSD symptom severity and physical functioning (31)(32)(33). Furthermore, four studies evaluated the association between PTSD with depression comorbidity and physical functioning (32,(34)(35)(36).…”
Section: Brooks Et Al (45) (2008)mentioning
confidence: 99%
“…Studies have demonstrated both high levels of PTSD symptom severity among patients with chronic pain [54] and high rates of chronic pain among patients with PTSD [16][17]55]. PTSD symptom severity has been associated with poorer health functioning among OIF/OEF veterans [56][57]. Additionally, PTSD symptom expression has been shown to differ between pain and pain-free populations [58].…”
Section: Discussionmentioning
confidence: 99%
“…Veterans with posttraumatic stress symptoms have been shown to have worse functioning than veterans without posttraumatic stress symptoms across a multitude of outcomes Jakupcak, Luterek, Hunt, Conybeare, & McFall 2008 ;Kashdan, Uswatte, Steger, & Julian, 2006 ;Vasterling, Schumm, Proctor, Gentry, King, & King, 2008 ;Yehuda et al, 1995 ). This has important diagnostic and treatment implications for the veteran population.…”
mentioning
confidence: 99%